2021
DOI: 10.3390/genes12050633
|View full text |Cite
|
Sign up to set email alerts
|

miR-542-3p Contributes to the HK2-Mediated High Glycolytic Phenotype in Human Glioma Cells

Abstract: (1) Background: The elevation of glucose metabolism is linked to high-grade gliomas such as glioblastoma multiforme (GBM). The high glycolytic phenotype is associated with cellular proliferation and resistance to treatment with chemotherapeutic agents in GBM. MicroRNA-542-3p (miR-542-3p) has been implicated in several tumors including gliomas. However, the role of miR-542-3p in glucose metabolism in human gliomas remains unclear; (2) Methods: We measured the levels of cellular proliferation in human glioma cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…High expression of miR‐1258 , miR‐935 and miR‐128‐3p was associated with better overall survival (OS) in patients with GBM, 23 , 24 , 25 while low miR‐542‐3p and miR‐221/222 clusters expression was associated with better OS in patients with GBM. 26 , 27 Previous studies evaluated the effect of cell‐free circulating RNA on patients with GBM. Nadaradjane et al 28 found that miR‐370‐3p could be treated in patients with GBM by enhancing temozolomide sensitivity, while it could not be used as a cell‐free circulating biomarker and was not associated with patient OS.…”
Section: Microrna Smentioning
confidence: 99%
See 2 more Smart Citations
“…High expression of miR‐1258 , miR‐935 and miR‐128‐3p was associated with better overall survival (OS) in patients with GBM, 23 , 24 , 25 while low miR‐542‐3p and miR‐221/222 clusters expression was associated with better OS in patients with GBM. 26 , 27 Previous studies evaluated the effect of cell‐free circulating RNA on patients with GBM. Nadaradjane et al 28 found that miR‐370‐3p could be treated in patients with GBM by enhancing temozolomide sensitivity, while it could not be used as a cell‐free circulating biomarker and was not associated with patient OS.…”
Section: Microrna Smentioning
confidence: 99%
“… 19 , 34 , 35 Previous studies have found that miR‐27a‐3p can also enhance the resistance of patients with GBM to temozolomide, which is closely associated with poor OS. 34 In addition, Kim et al 27 found that miR‐542‐3p could induce the glycolytic activity of GBM cells by activating hexokinase 2, thus promoting cell proliferation and chemotherapy resistance, leading to reduced OS in patients.…”
Section: Microrna Smentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-9-1 targets HK2 to inhibit glycolysis, reduce the formation of lactic acid, and promote metabolic reprogramming in nasopharyngeal carcinoma cells (Xu Q. L. et al, 2021). Meanwhile, miR-542-3p elevates HK2 to induce glycolysis in GBM (Kim et al, 2021). miRNA-1185-2-3p inhibits Golgi phosphoprotein 3 (GOLPH3L) and affects central carbon metabolism regulated by GOLPH3L (Xu et al, 2021b).…”
Section: Non-coding Ribonucleic Acidsmentioning
confidence: 99%
“…MiR-542 acts as a tumor-suppressor in human malignancies e.g., liver cancer, by regulating the expression of specific molecular targets [9]. There are limited reports on the regulatory role of miR-542 in human glioma [10]. The present study was carried out to investigate the role of miR-542 in glioma cells.…”
Section: Introductionmentioning
confidence: 99%